EXPLAINING TAX COMPLIANCE COSTS: DOES INFORMATION ASYMMETRY REALLY EXIST? - Al Rasyid, Rafi'i Habib; Purani; Winarni, Sri; Rahmadian, Succi (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2026)
Taxpayers bear additional burdens beyond the nominal amount of tax paid, commonly referred to as tax compliance costs. Drawing on information asymmetry theory, this study aims to explore factors that affect tax compliance costs. This study uses convenience sampling techniques to get 122 respondents, entrepreneurs, and independent professionals around Indonesia. Questionnaire sent by word of mouth and social media, using an online questionnaire platform. This study applies Partial Least Squares Structural Equation Modeling (PLS-SEM) the results indicate that tax knowledge, tax information, and tax complexity are significantly associated with tax compliance costs. These findings suggest that low levels of tax knowledge have the potential to increase tax compliance costs. In addition, the complexity of the tax system and unequal access to tax information may further increase the compliance costs. The results of this study provide a basis for policymakers to design a more efficient tax system.